Code Mixing in Parent’s Bilingualism for Developing English Children Literacy - Testiana Deni Wijayatiningsih; Riana Eka Budiastuti; Mustasyfa Thabib Kariadi; M. Riyanton; Dini Anggraheni (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This case study aims at analyzing the bilingualism Indonesian-English code mixing in parents’ day-to-day talk toward children’s literacy development in learning English. The areas of analysis in this bilingualism study include code-mixing categories: intra-sentential, intra-lexical, and changing dictions. Further, those areas give impacts to the children’s literacy development. The findings indicate that the parent is a bilingual who used Indonesian and English equally well. She is accustomed to do conversation by mixing two different languages to her children. In the conversation, the children are able to imitate and remember the words and phrases produced by parent. Further, this study also finds that the ways children attempt to master language are noticeable that they were expected to be able to mix two languages appropriately in their activities. Briefly, the children and their parent do bilingualism to support their literacy development in learning English.